Response of Autologous Serum Supratarsal Injection in Patients of Vernal Keratoconjunctivitis in Longterm Followup - Ritu Agarwal; Jai Shree Murli Manoher (Delhi Journal of Ophthalmology)
Purpose: To study the response of 0.1 ml autologous serum supratarsal injection in patients of vernal keratoconjunctivitis in their long term followup. Materials and Methods: This prospective, nonrandomized study was carried out in 50 patients of either sex and any age suffering from vernal keratoconjunctivitis. Previous medications were discontinued for period of 15 days before commencing serum injection. 0.1 ml of autologous serum was injected in each eye supratarsaly. Injection was repeated every week for 8 weeks and follow up of all patients was done at one month, three months, six months and one-year interval. Results: Significant improvements in symptoms and some of the signs were achieved. Improvement was significant even after discontinuation of treatment. No additional medications were required. Conclusions: 0.1 ml supratarsal injection of autologous serum is an effective alternative treatment in vernal for long term and without any adverse effects.